A Potential New Technique to Estimate the Origins of Focal Atrial Tachycardias from 12-Lead Electrocardiograms - F.Babbs, Charles (Journal of Hypertension and Cardiology, 2016)
Background: This brief report presents a potential new technique for locating the sites of origin of focal atrial tachycardias from standard 12-lead electrocardiograms. Methods: Estimated P wave vector coordinates are derived from leads I, aVF, V1 and V2, and mapped to a three dimensional coordinate system in space. A simple graphical method is used to find the back projection of the P wave vector onto the surface of atrial muscle to estimate the most likely site of origin of the tachycardia. Results: Graphical back projection correctly identified foci of atrial tachycardias in 19 of 19 cases described in the most complete available published study. Conclusions: Clinical studies are indicated to validate this simple method for initial noninvasive evaluation of candidates for ablation therapy.
Keywords: Ablation; algorithm; foci; supraventricular tachycardia; vector